Overall survival of colorectal cancer by stage at diagnosis: Data from the Martinique Cancer Registry. Issue 35 (August 2019) - Joachim, Clarisse; Macni, Jonathan; Drame, Moustapha; Pomier, Audrey; Escarmant, Patrick; Veronique-Baudin, Jacqueline; Vinh-Hung, Vincent
Abstract : Abstract: Population-based cancer registries (PBCR) participate in epidemiological surveillance and in the evaluation of cancer types by enabling analysis of incidence and survival data over time. The aim of this study was to examine overall survival (OS) in patients with colorectal cancer (CRC) by analyzing data from the Martinique population-based cancer registry between 1993 and 2012. All colorectal cancer cases diagnosed in Martinique between 1993 and 2012 were included. Characteristics of CRC patients were analyzed according to age subgroups, namely: <50 years, 50 to 74 years and over 75 years. We recorded the following socio-demographic and clinical variables: year of diagnosis, age at diagnosis, sex, histology, zone of residence, and subsite of the cancer. Incidence of malignant neoplasms of the colon and rectum (ICD-10 C18–21) was extracted from the Martinique Cancer Registry database. Stage at diagnosis (localized: stage I–II, regional: stage III and metastatic stage: stage IV) were also analyzed for the 2008 to 2012 period. A total of 2230 cases of incident invasive CRC were included during the study period (1993–2012): 1171 were women (52.5%); 1588 patients (71.2%) had colon cancer. Stage at diagnosis was evaluated in 779 patients (89.6%): 486/779 (62.4%) had stage III–IV at diagnosis, including 285 (36.6%) patients with metastases at diagnosis (stage IV). One-year, 5-year and 10-year OS for the study period 1993 to 2012 was 74.6%, 43.8% and 33.0% respectively. There was a statistical difference in overall survival according to gender ( P = .0153), age at diagnosis ( P < .001) and stage ( P < .001). Median OS was 2.0 years (95% CI [1.4–2.1]) in the stage III–IV group during the period 2008 to 2012, whereas it was unreached in the stage I–II group. Multivariable analysis confirmed that stage III–IV at diagnosis (hazard ratio (HR) = 3.70 [2.89–4.99]; P < .0001) and colon cancer (HR = 1.30 [1.01–1.69]; P = .04) were main prognostic factors for OS. Women had a HR of 0.78 [0.62–0.96], P = .02. CRC patients in the 50 to 74 years age group had a HR of 0.63 [0.50–0.80], P = .0001. This study underlines the importance of structuring management of CRC cancer patients.